2012
DOI: 10.1155/2012/809587
|View full text |Cite
|
Sign up to set email alerts
|

Sesame (Sesamum indicumL.) Growth and Yield as Influenced by Preemergence Herbicides

Abstract: Studies were conducted during the 2007 and 2008 growing seasons under weed-free conditions in South Texas and the High Plains region of Texas to evaluate preemergence herbicides for sesame tolerance. No reduction in sesame stand was noted with any herbicide at south Texas location; however, at the High Plains location, linuron at the 2X rate reduced stand counts 28 days after treatment (DAT) in 2007 and diuron reduced sesame stand 147 DAT in 2008 when compared with the untreated check. At the 1/2X rate all her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The causes are as follows: Psychological stress, physiological stress which occurs in conditions like shock, severe trauma, extensive burn (Curling's ulcer), septicaemia, cushing's ulcer. 4 The pathology of the stress ulcer is not clear, the possible hypotheses for genesis of stress ulcers is Ischaemic hypoxic injury to the mucosal cells and depletion of the gastric mucus barrier rendering the mucosa susceptible to attack by acid-peptic secretions. 4 In the present study the ulcer induction was done using restraint cage and placing the rats in cold ventilated freezer for 2 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes are as follows: Psychological stress, physiological stress which occurs in conditions like shock, severe trauma, extensive burn (Curling's ulcer), septicaemia, cushing's ulcer. 4 The pathology of the stress ulcer is not clear, the possible hypotheses for genesis of stress ulcers is Ischaemic hypoxic injury to the mucosal cells and depletion of the gastric mucus barrier rendering the mucosa susceptible to attack by acid-peptic secretions. 4 In the present study the ulcer induction was done using restraint cage and placing the rats in cold ventilated freezer for 2 hours.…”
Section: Discussionmentioning
confidence: 99%
“…4 The pathology of the stress ulcer is not clear, the possible hypotheses for genesis of stress ulcers is Ischaemic hypoxic injury to the mucosal cells and depletion of the gastric mucus barrier rendering the mucosa susceptible to attack by acid-peptic secretions. 4 In the present study the ulcer induction was done using restraint cage and placing the rats in cold ventilated freezer for 2 hours. Edward et al, studied the Synergism between cold and restraint for rapid production of stress ulcers in rats and they observed that restraint and exposure to cold acted synergistically to produce gastric ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…With weak seedling vigor, limited competitive ability, and a lack of inexpensive and affordable labor, the use of preemergence (PRE) and/or postemergence (POST) herbicides are essential for commercial mechanized sesame production, especially in the U S [6][7][8][9]. Also, the long growing season for sesame requires a weed management program that provides season-long weed control [6,8,18]. Currently, S-metolachlor is the only herbicide registered for PRE use in the U S and sesame injury has been observed with this treatment under certain conditions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the long growing season for sesame requires a weed management program that provides season-long weed control [6,8,18]. Currently, S-metolachlor is the only herbicide registered for PRE use in the U S and sesame injury has been observed with this treatment under certain conditions [18]. In Texas, S-metolachlor resulted in 9 to 29% sesame stand reduction at one location and < 8% at a different location [18].…”
Section: Introductionmentioning
confidence: 99%
“…Sesame (Sesamum indicum: Pedaliaceae) is a food plant that is hardy and drought tolerant (Bedigian and Harlan, 1986;Sintim and Yeboah-Badu, 2010). It was mostly grown in Africa and Asia but has recently been introduced into the USA (Grichar et al, 2012) in places such as Texas where cotton failed due to erratic rainfall (Betts, 1999). In sesame, the lignans, sesamin, sesamolin, sesamol (Van Dijk et al, 1973), secoisolariciresinol, lariciresinol, matairesinol, and pinoresinol (Midler et al, 2005), have been reported as constitutive components of the seed.…”
Section: Introductionmentioning
confidence: 99%